To the question of reliability and durability ballastless deck of bridge - Prystynskaya, V. V. (Science and Transport Progress, 2012)
The principal causes of operational defects in bridge ballastless deck plates are considered in the article. The drawbacks of these plates construction that prevent from achieving a higher level of bridge framework reliability and durability have been analysed.